2016
DOI: 10.1136/bmjopen-2016-011028
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre randomised placebo-controlled trial of oral anticoagulation with apixaban in systemic sclerosis-related pulmonary arterial hypertension: the SPHInX study protocol

Abstract: IntroductionSystemic sclerosis (SSc) is a severe and costly multiorgan autoimmune connective tissue disease characterised by vasculopathy and fibrosis. One of the major causes of SSc-related death is pulmonary arterial hypertension (PAH), which develops in 12–15% of patients with SSc and accounts for 30–40% of deaths. In situ thrombosis in the small calibre peripheral pulmonary vessels resulting from endothelial dysfunction and an imbalance of anticoagulant and prothrombotic mediators has been implicated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 73 publications
0
9
0
2
Order By: Relevance
“…1 An Australian multicenter RCT SPHInx evaluating the administration of apixaban vs. placebo in SSc-PAH is currently ongoing. 73 Ongoing clinical trials…”
Section: Anticoagulationmentioning
confidence: 99%
“…1 An Australian multicenter RCT SPHInx evaluating the administration of apixaban vs. placebo in SSc-PAH is currently ongoing. 73 Ongoing clinical trials…”
Section: Anticoagulationmentioning
confidence: 99%
“…The SPHYNX trial aims to assess the efficacy, safety, and cost-effectiveness of treatment with apixaban in PAH associated with scleroderma over 3 years, in a multicenter, double-blind, placebo-controlled randomized controlled trial. 42 Of note, the SPHYNX trial includes a cost-effectiveness analysis, and will be able to infirm the results of a previous medico-analytic study which suggested a positive effect of anticoagulant therapy in patients with idiopathic PAH but not PAH associated with scleroderma. 43 The Pragmatic Clinical Trials in Scleroderma Note: The table shows a summary of data obtained from prospective studies, regarding the efficacy and safety of anticoagulant therapy in patients with pulmonary arterial hypertension (PAH) orchronic thromboembolic pulmonary hypertension (CTEPH).…”
Section: Unmet Needs Recent Advances Ongoing Studies Determining Thmentioning
confidence: 88%
“…48 There is an ongoing trial (SPHInX) that aims to evaluate the efficacy and safety of apixaban, a direct oral anticoagulant, in SSc-PAH. 100…”
Section: Oral Anticoagulationmentioning
confidence: 99%